2009
DOI: 10.1111/j.1749-6632.2009.03857.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Connection between Lateral and Posterior Semicircular Canal Revealed by a New Modeling Process

Abstract: We developed a modeling procedure using CT scans or MRI data for exploring the bony and lymphatic canals of vestibular patients. We submitted 445 patients with instability and spatial de-orientation to this procedure. Out of the 445 patients, 95 had scoliosis, some of them, because malformations were suspected also had CT-scan modeling and functional tests. We focused on a never described, abnormal connection between the lymphatic lateral and posterior canal (LPCC) with a frequency of 67/445 (15%). In the scol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…For instance, Shi et al [28] observed a decrease in the distance between centers of lateral and superior canals in the leftside vestibular system. Results from another study have confirmed morphological abnormalities in patients with AIS with small curve deformity [13]. Overall, these results suggest that spine deformity may occur due to malformation of the vestibular apparatus.…”
Section: The Vestibular Systemmentioning
confidence: 53%
See 1 more Smart Citation
“…For instance, Shi et al [28] observed a decrease in the distance between centers of lateral and superior canals in the leftside vestibular system. Results from another study have confirmed morphological abnormalities in patients with AIS with small curve deformity [13]. Overall, these results suggest that spine deformity may occur due to malformation of the vestibular apparatus.…”
Section: The Vestibular Systemmentioning
confidence: 53%
“…Consequently, during the last decades, several authors have suggested that scoliosis onset may be related to impairment of the vestibular system because of its contribution to regulation of axial muscles tone e.g. [5,[11][12][13]. Nonetheless, no study has addressed whether direct vestibular stimulation would lead to abnormal motor response in patients with AIS compared to controls.…”
Section: Introductionmentioning
confidence: 95%
“…One of AIS etiological hypotheses is that the scoliotic deformation is the result of orthostatic postural control disorder, with a disturbance of internal representation of the gravitational vertical [6]. Thus, the vestibular system is the most studied sensory modality [6,[9][10][11], because it has an important role in orthostatic postural control, and measures the earth gravitational vector directly. An asymmetric disturbance of the vestibular system leads to an asymmetric activity of vestibular-spinal tract, and an asymmetric paravertebral muscle tone, which, in growing adolescent results in a scoliotic deformity [10].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the vestibular system is the most studied sensory modality [6,[9][10][11], because it has an important role in orthostatic postural control, and measures the earth gravitational vector directly. An asymmetric disturbance of the vestibular system leads to an asymmetric activity of vestibular-spinal tract, and an asymmetric paravertebral muscle tone, which, in growing adolescent results in a scoliotic deformity [10]. This is Evaluation impossible due to psychic, social or geographical problems, or inability to understand Physical examination shows measurable gibbous deformity on the forward bending test [28] confirmed by experiments in animals [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation